2015
DOI: 10.1007/s12031-015-0497-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction

Abstract: The purpose of this meta-analysis was to investigate the correlation between serum homocysteine (Hcy) levels and the pathogenesis of cerebral infarction (CI). Relevant studies involving serum Hcy levels and the pathogenesis of CI were identified using electronic database search supplemented with manual search. The search result studies were screened in accordance with our strict inclusion and exclusion criteria. Statistical analyses were conducted with Comprehensive Meta Analysis 2.0 (CMA 2.0) software. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Heterogeneity decreased significantly on subgroup analyses by region and controlling for smoking. The inconsistency by region subgroup may be related to factors such as the different environment, lifestyles, living conditions, and constitution of Europe, North America and other regions [28]. As for controlling for smoking, the inconsistency can be interpreted as elevated plasma Hcy level being influenced by smoking [29], and smoking can increase the risk of stroke [30].…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity decreased significantly on subgroup analyses by region and controlling for smoking. The inconsistency by region subgroup may be related to factors such as the different environment, lifestyles, living conditions, and constitution of Europe, North America and other regions [28]. As for controlling for smoking, the inconsistency can be interpreted as elevated plasma Hcy level being influenced by smoking [29], and smoking can increase the risk of stroke [30].…”
Section: Discussionmentioning
confidence: 99%
“…The US National Institutes of Health Stroke Scale was used to assess the severity of cerebral infarction patients. Mild cerebral infarction: 2–4 points, moderate cerebral infarction: 5–20 points, severe cerebral infarction: >21 points (7).…”
Section: Methodsmentioning
confidence: 99%
“…Temple et al [16] found that the plasma Hcy levels in 30-40% of the patients with cerebral infarction were elevated. Other studies also showed that Hhcy was associated with the recurrence of cerebral infarction [14,17]. However, the association of Hhcy levels with cerebral infarction recurrence has not been systematically assessed.…”
Section: Introductionmentioning
confidence: 99%